The Effect Of Moringa Oleifera Leaf Extract On Fibroblast Cell Migration And Morphology In In Vitro Nih/3t3 Cell Line Culture - Mawar Subangkit Mawar Subangkit; Made Intan Dwijayanti; Elpita Tarigan; Yusa Irarang; Sindi Farhana (CV. AFDIFAL MAJU BERKAH, 2026)
Moringa oleifera leaves are widely recognized for containing flavonoid and phenolic compounds with the potential to promote wound healing by stimulating fibroblast activity. This study aimed to evaluate the effects of Moringa oleifera leaf extract on the migration and morphological changes of NIH/3T3 fibroblast cells using an in vitro wound model. The experiment employed the scratch wound healing assay with five extract concentrations (12.5, 25, 50, 100, and 200 µg/mL) and one untreated control group (Blank). Observations were conducted on days 0, 1, and 2 using an inverted microscope. Image quantification was performed with ImageJ, and non-parametric statistical analysis (Kruskal–Wallis test) was conducted using RStudio. The evaluated parameters included cell count, cell density in the peripheral wound area, and four cell morphometric parameters (solidity, circularity, roundness, and aspect ratio). The results demonstrated a significant difference in cell count among treatment groups (p = 0.00072), with the 50 and 100 µg/mL groups showing the most consistent increase in cell number on days 1 and 2. The solidity parameter also differed significantly among treatment groups at each observation time point (p = 0.0014), whereas circularity, roundness, and aspect ratio exhibited significant differences in pairwise group comparisons despite the overall Kruskal–Wallis test not reaching statistical significance. Cell density in the peripheral wound area did not differ significantly among groups (p = 0.24). The 200 µg/mL concentration consistently showed the lowest cell count and cell density on day 2, suggesting a potential cytotoxic effect at high doses. These findings support a biphasic (hormetic) dose–response pattern, with concentrations of 50–100 µg/mL providing the most consistent stimulation of fibroblast cell migration and morphological changes, closely resembling the activated healthy cell phenotype observed in the untreated control group.